THE PREVALENCE OF TUBERCULOSIS IN CATTLE AND THEIR HANDLERS IN NORTH TONGU, VOLTA REGION, GHANA - Amemor, Esther A.; Sackey, S. O.; Yebuah, Nathaniel; Folitse, Raphael Deladem; Emikpe, Benjamin O.; Afar, E.; Wurapa, F.; Ohuabunwo, C.; Addo, K.; Mensah, David; Gaglo, E.; Hansen, Mark; et al. (African Journal of Infectious Diseases (AJID), 2016)
Background: The need to understand the contribution of bovine tuberculosis (BTB) to the general tuberculosis burden in a poor resource setting is paramount. The aim of this study is to determine the burden of BTB among herdsmen and cattle in the North Tongu district of Volta Region in Ghana. Materials and Methods: A cross- sectional study was conducted in the North Tongu District of the Volta Region between the period of October 2011- March 2012. A well-structured questionnaire was used to collect socio-demographic information and possible risk factor information on cattle from participants. Sputum samples from 68 herdsmen and blood samples from 200 cattle belonging to these herdsmen were also collected. Sputum samples were analyzed using Ziehl- Neelsen staining while Anigen Rapid BTB Test was used for Cattle blood samples. Results: Ninety percent (61/68) of respondents were also found to consume fresh milk while 84% (57/68) do not use protective clothing. Of a total of 1580 cattle owned by the herdsmen, 200 cattle consisting of 14 bulls and 186 cows were screened where the prevalence of bovine TB was 19% (38/200) and those affected were all females. All (100%) human sample tested negative for Acid- Fast Bacilli (AFB). However, the seropositivity of cattle and kraal density were statistically associated (p= 0.001). Conclusion: Bovine TB is prevalent in cattle in North Tongu district. Although herdsmen indulge in risky lifestyles that expose them to BTB, a zero prevalence of BTB was observed, further study is envisaged using a larger sample size.